2017
DOI: 10.1002/cbic.201700521
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of PRMT1 Reveals Multifactorial Processivity and a Sequential Ordered Mechanism

Abstract: Arginine methylation is a prevalent post‐translational modification in eukaryotic cells. Two significant debates exist within the field: do these enzymes dimethylate their substrates in a processive or distributive manner, and do these enzymes operate using a random or sequential method of bisubstrate binding? We revealed that human protein arginine N‐methyltransferase 1 (PRMT1) enzyme kinetics are dependent on substrate sequence. Further, peptides containing an Nη‐hydroxyarginine generally demonstrated substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 73 publications
(166 reference statements)
2
8
0
Order By: Relevance
“…This may explain why certain steady-state kinetic studies showed that PRMT catalysis follows an ordered sequential mechanism. [27f,g,29] Together, we believe that our transient kinetic model provides a mechanistic explanation that unifies the seemingly contradictory steady-state kinetic studies reported in the literature.…”
Section: The Kinetic Model Of Prmt Catalysissupporting
confidence: 74%
See 2 more Smart Citations
“…This may explain why certain steady-state kinetic studies showed that PRMT catalysis follows an ordered sequential mechanism. [27f,g,29] Together, we believe that our transient kinetic model provides a mechanistic explanation that unifies the seemingly contradictory steady-state kinetic studies reported in the literature.…”
Section: The Kinetic Model Of Prmt Catalysissupporting
confidence: 74%
“…On the other hand, when low‐affinity peptide substrates are used, the contribution of enzyme‐substrate binding (i. e., E‐H4 formation) would be negligible and can be ignored in the kinetic scheme, in which case the steady‐state kinetics would behave like a standard ordered sequential mechanism. This may explain why certain steady‐state kinetic studies showed that PRMT catalysis follows an ordered sequential mechanism ,,. Together, we believe that our transient kinetic model provides a mechanistic explanation that unifies the seemingly contradictory steady‐state kinetic studies reported in the literature.…”
Section: The Kinetic Model Of Prmt Catalysissupporting
confidence: 69%
See 1 more Smart Citation
“…al. for PRMT1 [ 21 ]. We found that switching the terminal aminomethyl (TP-064) to a methoxy moiety to obtain N-((2-(1-(2-methoxyethyl)piperidin-4-yl)pyridin-4-yl)methyl)-N-methyl-3-phenoxybenzamide (TP-064N) clearly reduced the inhibitory activity against PRMT4 (IC 50 2.5 ± 0.6 μM; Figure 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…PRMT5 is the predominant type II enzyme ( Stopa et al., 2015 ). Importantly, while PRMT1 and PRMT9 have been shown to exhibit semi-processivity ( Brown et al., 2018 ; Gui et al., 2013 ; Jain et al., 2016 ; Osborne et al., 2007 ), PRMT enzymes are generally distributive ( Burgos et al., 2015 ; Hu et al., 2016 ; Jacques et al., 2016 ; Lakowski and Frankel, 2008 , 2009 ; Obianyo et al., 2008 ; Wang et al., 2013 , 2014 ) and are capable of scavenging each other's substrates ( Dhar et al., 2013 ). These observations suggest a complex enzyme/substrate interplay and imply potentially complementary cellular roles.…”
Section: Introductionmentioning
confidence: 99%